Effect Observation of Optimized Individualized Nursing Care Applied to ICU Patients with Severe Pneumonia - Xianpeng Wang; Yimei Qiu; Ting Xu; Yufeng Chen; Chunxiao Ying (Emergency Medicine International)
Purpose. This study aims to observe the effect of optimized individualized nursing care applied to intensive care unit (ICU) patients with severe pneumonia (SP). Methods. 440 patients with SP admitted to the ICU of our hospital from January 2019 to June 2020 were provided with routine nursing care (group A), and 550 patients with SP admitted from July 2020 to December 2021 were provided with optimized individualized nursing care (group B). The blood lactate index and acute physiology and chronic health evaluation (APACHE II) scores before and after care were compared between the two groups. The WBC count recovery time, mechanical ventilation time, antipyretic time, and length of hospital stay of the two groups were recorded. The complication rate of the two groups during the nursing care period was compared. The prognosis effect of the two groups after 6 and 12 months of discharge was followed up with the Seattle angina pectoris questionnaire (SAQ). Results. After care, the lactate level and lactate clearance rate were higher in both groups than before care, and the lactate level in group B was lower than that in group A and the lactate clearance rate was higher than that in group A (P<0.05). After care, APACHE II scores were lower in both groups than before care, and lower in group B than in group A (P<0.05). After care, the WBC count recovery time, mechanical ventilation time, antipyretic time, and length of hospital stay were shorter in group B than in group A (P<0.05). During the nursing care period, the complication rate was lower in group B (5.82%) than in group A (11.59%) (P<0.05). 6 and 12 months after discharge, the SAQ scores were higher in group B than in group A (P<0.05). Conclusion. Optimized individualized nursing care applied to ICU SP patients can effectively improve the patients’ physiological indicators, reduce complications, improve the prognosis of quality of life, and have a positive effect on the patients’ speedy recovery.